GAMBARAN PERSEPSI PEKERJA TENTANG RISIKO KECELAKAAN KERJA DI DEPARTEMEN PRODUKSI DAN UTILITY PT. WILMAR NABATI INDONESIA DUMAI TAHUN 2012 - Erzain Vesta (Lingkungan dan Kesehatan Kerja, 2014)
Overview Of Worker's Perception Of Risk Of Occupational Accidents In Production And Utility Department PT. Wilmar Nabati Indonesia Dumai in 2012. Perception is a factor that affects the behavior. Perception of risk is a process by which individuals interpret information they receive about the risk. If a person's perception of risk is poor, its behavior tend to ignore the risk of exposure. The purpose of this research is knowing an overview about worker's perception of risk of occupational accidents in Production and Utility Department PT. Wilmar Nabati Indonesia Dumai in 2012. This kind of research is descriptive quantitative approach. The number of samples obtained by 42 people with total sampling. Primary data obtained from interviews using the questionnaire in two departments. Secondary data about an overview of company were obtained from HR department and EHS PT. Wilmar Nabati Indonesia Dumai and Pelintung. Data were analyzed descriptively. From the results of research obtained from the 42 respondents that as many as 37 people (88,1%) have a good perception about the risk of occupational accidents and 5 (11.9%) have a poor perception about the risk of occupational accidents. Respondents have a poor perception of the risk of accidents in the workplace and the prevention of accidents. Researchers suggested that companies provide safety training on the identification of the potential hazards in the workplace and the prevention of accidents for all their workers to improve knowledge of worker about safety in work. Companies should also improving monitoring at the workplace with respect to the compliance of workers in the use of personal protective equipment. Keywords: Workers, Perceptions, Risk of Occupational Accidents